AN ANALYSIS OF STUDENTS’ SPEECH ABILITY AND DIFFICULTIES IN PUBLIC SPEAKING - Astriani, Riza; Wahyuningsih, Destri; Roswati, Roswati; Nurdiana, Nurdiana (J-Shelves of Indragiri (JSI), 2023)
Public speaking is an art of speaking in public or about a certain matter or topic orally with the goal of influencing, inviting, educating, changing opinions, giving explanations and providing information. The purpose of this research is to find out the students’ ability in speech material and to explain kinds of the factors that influence the students’ speech difficulties in public speaking. In this study, the researcher used Descriptive qualitative research method design. The kind of this research was gathered through instruments of the research: observation sheet to determine types of speech and method of speech will be used while giving a speech, interview students’ difficulties and documentation. The researcher obtained the students’ ability were 71% for the fourth semester students and 70, 5% for the sixth semester students who interest in English speech. The researcher found the students’ difficulties in Public Speaking, based on the interview questions that have been answered based on the factors are Pronunciation, Grammar, and Fluently, another difficulties are lack of self-confidence and not mastering the materials. Key words: Analysis, Speech, Ability, Difficulties, Public Speaking